1994
DOI: 10.1148/radiology.191.3.8184076
|View full text |Cite
|
Sign up to set email alerts
|

Perflubron as an oral contrast agent for MR imaging: results of a phase III clinical trial.

Abstract: Perflubron is safe, and its efficacy was unaffected by pulse sequences, magnetic field strength, or time delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Traditional barium meals provide contrast in CT, and virtual colonoscopy is competing with traditional fiber optic probes [388]. MR procedures have lagged behind CT, but several potential contrast agents have been presented, ranging from paramagnetic zeolite formulations [389] and ferric ammonium citrate [390] to PFC emulsions [391,392] and recently images were shown in mice based on perfluorononane [69].…”
Section: Passive Reporter Moleculesmentioning
confidence: 99%
“…Traditional barium meals provide contrast in CT, and virtual colonoscopy is competing with traditional fiber optic probes [388]. MR procedures have lagged behind CT, but several potential contrast agents have been presented, ranging from paramagnetic zeolite formulations [389] and ferric ammonium citrate [390] to PFC emulsions [391,392] and recently images were shown in mice based on perfluorononane [69].…”
Section: Passive Reporter Moleculesmentioning
confidence: 99%
“…For MRI, the multi-resonance spectrum requires extensive editing. PFOB has been tested in clinical trials [276,277] and recently images were shown in mice based on 5. METABOLISM AND DRUG UPTAKE perfluorononane [278].…”
Section: Hypoxia Hypoxic Fraction and In Vivo Nitroreductase Activitimentioning
confidence: 99%
“…Since the magnetic properties of 19 Ffluorocarbons correlate with organ oxygen content, perfluorocarbons tagged with 19 F can be used as diagnostic tools to assess tissue oxygenation by magnetic resonance imaging [46,47]. In addition, some perfluorocarbons can also be used as contrast agents in sonography, computed tomography, and conventional radiology [48,49]. In the area of hemoglobinbased oxygen carriers further interesting developments will result from advances in biotechnology.…”
Section: Experimental Use Of Artificial Oxygen Carriersmentioning
confidence: 99%